“Yenisei Meridian” of the Old Believers: methods of research of the ethno-confessional environment - Prigarin, Alexander A.; Storozhenko, Alena A. (The New Research of Tuva, 2024)
The article analyzes the results of cameral and field studies of Old Believer communities in Tuva and the entire Yenisei Siberia conducted during 2016–2020 by a group of researchers affiliated with leading scientific institutions and regional research and educational centers in Russia. The methodological approaches and methods tested by the research team within the framework of joint and individual grant projects are systematized. The historical approach facilitated an assessment of the origins, causes, and nature of the temporal evolution of the processes under study. The ethnological approach focused on evaluating the dynamics of ethnic parameters within Old Believer culture, as well as the extent and character of its mutual influence with the external environment, including the autochthonous milieu. A religious studies perspective on the issue of regional Old Believers helped uncover the depth of specific features of confessional development in life and worldview of taiga Old Believers and their spectrum of communication. The cultural studies perspective contributed to contextual assessments of the general trajectory of cultural development in the studied community and its key distinctive characteristics. Methods of socio-cultural anthropology allowed for the synthesis of various social and cultural parameters of the studied group and helped determine the place, role, and significance of individuals within this complex system. The study identified the principles of traditionalism and group confessional consolidation among the Old Believers of the “Yenisei Meridian” as being rooted in conservatism, along with their cultural and everyday isolation. The dominance of the “field” approach became a leading research principle, resulting in significant clarifications of the social practices of this ethno-confessional group.